Somatotopy in the Human Somatosensory System - Sanchez Panchuelo, Rosa M.; Besle, Julien; Schluppeck, Denis; Humberstone, Miles; Francis, Susan (Frontiers in Human Neuroscience, 2018)
Previous functional magnetic resonance imaging (fMRI) studies have demonstrated digit somatotopy in primary somatosensory cortex (SI), and even shown that at high spatial resolution it is possible to resolve within-digit somatotopy. However, fMRI studies have failed to resolve the spatial organization of digit representations in secondary somatosensory cortex (SII). One of the major limitations of high spatial resolution fMRI studies of the somatosensory system has been the long acquisition time needed to acquire slices spanning both SI and SII. Here, we exploit the increased blood oxygenation level dependent contrast of ultra-high-field (7 Tesla) fMRI and the use of multiband imaging to study the topographic organization in SI and SII with high spatial resolution at the individual subject level. A total of n=6 subjects underwent vibrotactile stimulation of their face, hand digits and foot (body imaging) and their individual hand digits (digit mapping) for each left and right sides of the body. In addition, n=2 subjects participated only in the body imaging experiment on both their left and right sides. We show an orderly representation of the face, hand digits and foot in contralateral primary cortex in each individual subject. In the secondary somatosensory cortex, there is clear separation of the body areas of the face, hand and foot but the spatial organization varies across individual subjects. However, separate representation of the individual digits of the hand in SII could not be resolved, even at the spatial resolution of 1.5 mm due to largely overlapping representations.